"We don't have a good system for people who don't have a home and don't need a hospital": Contextualizing the hospital discharge process for people experiencing homelessness in Toronto, Canada - Jesse I.R. Jenkinson; Stephen W. Hwang; Carol Strike; Erica Di Ruggiero (Elsevier, 2022)
Hospital discharge is a key transition in a patient's care pathway, providing an effective point of intervention to address a patient's ongoing health and social care needs. Addressing these needs may prevent hospital readmissions. The hospital discharge process for people experiencing homelessness who have been admitted for medical conditions has not been well-characterized. To address this gap in knowledge, we interviewed hospital and shelter workers, and key informants, about their experiences when unhoused patients are discharged from hospitals to shelters. Using critical realism, we explored the organizational and service context of this process by looking at the relationship between structures and agency in the daily work of our participants. Our results indicate that the discharge process for unhoused patients was shaped by two systems failures, barriers to publicly funded systems including community resources, and silos and gaps between these systems, ultimately leading to failed transitions to the community. The most prominent manifestations of these systems failures were a) limited and inadequate access to post-discharge care and services, b) barriers to accessing shelters, c) inadequate service integration between healthcare and social service sectors, and, d) poor cross-sectoral knowledge between hospital and shelter workers. We characterize the discharge process for unhoused patients as a part of a larger systems failure in the care for unhoused patients and contend that improvements in hospital discharges requires changes to underlying structures that lead to inadequate discharges.